S112 Mmp12 And Lmo7 Are Key Genes Involved In The Early Pathogenesis Of Squamous Cell Carcinoma Of The Lung. (10th November 2014) - Teixeira, VH; Lourenco, S; Falzon, M; Capitanio, A; Bottoms, S; Carroll, B; Brown, J; George, JP; Janes, SM
Abstract : Lung cancer is the most lethal cancer type worldwide. In order to improve patient survival it is important to enhance our understanding of the early changes associated with lung cancer progression. UCLH has a unique cohort of patients with pre-invasive lung squamous cell carcinoma (SCC) lesions. Within this cohort there is a discrepancy between the prevalence of pre-invasive lesions and the incidence of invasive lung cancer, which suggests that not all pre-invasive lesions progress to invasive carcinomas. The aim of this study was to identify and characterise key genes involved in the early pathogenesis of lung SCC. We performed genome-wide gene expression Illumina Whole-Genome DASL® arrays in 19 regressive and 20 progressive pre-invasive lung SCC lesions. The expression of matrix metallopeptidase 12 (MMP12) and LIM domain 7 (LMO7) was also determined in the 39 pre-invasive lung cancer lesions by immunostaining analysis. The functional role of MMP12 and LMO7 in cell migration and invasion was demonstrated by MMP12 and LMO7-knockdown in different squamous cell carcinoma cell lines and human bronchial epithelial cells (HBECs), respectively. We found 939 genes significantly differently expressed between the progressive and the regressive pre-invasive lung SCC lesions. We identified a remarkably elevated expression of a spectrum of genes in the progressive lung SCC lesions involved in different related cancer pathways including chromosome instability, p53 signalling and Wnt/β-catenin signalling. MMP12 and LMO7 were found within the highest significantly differently expressed genes and were therefore chosen to pursue studies focused on understanding the potential mechanisms leading to the development of lung SCC. In agreement with the gene expression data the expression of MMP12 and LMO7 proteins were up-regulated and down-regulated, respectively, in progressive when compared with regressive lesions. Inhibiting MMP12 by MMP12 knockdown significantly reduced the migration and invasion of different squamous cell carcinoma cell lines (A431, H357 and H376). We also established HBECs knockdown targeting LMO7. We observed a significant increase in the migration and invasion of HBECs cells in the LMO7 shRNA knockdown compared to control. Our results suggest that MMP12 and LMO7 may be potential therapeutic markers for lung cancer at early stage.